Inteligencia Artificial y valoración de la prueba: las garantías Jurídico-Constitucionales del órgano de control - Castellano, Pere Simón (2021)
Judicial proceedings and trials will be digital or they will not be. Overcoming the debate about the convenience of embracing the technological advance does not imply accepting integrated positions de facto. The COVID-19 pandemic has further highlighted the troubles and deficits of Spanish judicial proceedings. A slow justice, paralyzed due to remote work and without resources or guarantees to hold trials at a distance, is not justice. Excuses are running out today faster than ever, since new levels of effectiveness, efficiency, and speed, with full respect of procedural guarantees, can be reached with the use of most modern new technologies.This article explores the possibilities of using artificial intelligence systems in a specific area: the assessment of evidence. In this context, the hypothesis that the article aims to demonstrate is that although the human presence will continue to be necessary in judicial proceedings, artificial intelligence systems could support the free assessment of evidence by the judge and cover those gaps where the human mind shows its most erratic side, such as during corroborations.